2010
DOI: 10.1111/j.1475-097x.2010.01001.x
|View full text |Cite
|
Sign up to set email alerts
|

Left and right ventricular systolic long-axis function and diastolic function in patients with takotsubo cardiomyopathy

Abstract: Takotsubo cardiomyopathy temporarily affects systolic LV and RV function, while most diastolic parameters remain unchanged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
6
1
Order By: Relevance
“…These findings differ from the report by Loiske et al, (2011), in that conventional DF parameters were shown to improve over time, corrected or at least uncorrected. Likely, this is secondary to the higher sample size of ours.…”
Section: Figurecontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings differ from the report by Loiske et al, (2011), in that conventional DF parameters were shown to improve over time, corrected or at least uncorrected. Likely, this is secondary to the higher sample size of ours.…”
Section: Figurecontrasting
confidence: 99%
“…Substandard inclusion might be a contributing factor, for example incomplete (or incorrect) ICD coding regarding the U.S. study part. Although this is in line with many echocardiographic TTC studies, due to its elusive natural course, while we actually obtained results that could not be proven as significant previously (Loiske et al ., ), implying that our cooperation still paid off in this respect. It is important to recall, however, that the population size affects the degree of significance.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, we took only one blood sample and the routine use of intravenous diazepam before catheterization in our institution might have reduced catecholamine excretion [28]. Furthermore, ejection fractions as measured by echocardiography (recently published in detail elsewhere [29]) and MRi were reduced only moderately compared with findings by others [2,27]. We have no definite explanation to this difference; the timing of examinations in our study was identical to the previous ones and in line with these studies ejection fraction improved to normal.…”
Section: Discussionmentioning
confidence: 99%